1986
DOI: 10.1017/s0022226700010537
|View full text |Cite
|
Sign up to set email alerts
|

Government and code-mixing

Abstract: Please be advised that this information was generated on 2018-05-12 and may be subject to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(141 citation statements)
references
References 11 publications
2
132
0
4
Order By: Relevance
“…For example, Tami/English: Ellaam confused-aa irundadu (Annamalai, 1989, p. 50) is an instance of CS where the English morpheme "confused" is switched into the Tami sentential frame Researchers like Poplack (1980), Joshi (1985), DiSciullo, Muysken and Singh (1986), Appel and Muysken (1987), Gardner-Chloros (1987), Azuma (1991), Myers-Scotton (1993), Grosjean (1997), Myers-Scotton (1997, 2005), MacSwan (2000MacSwan ( , 2009, Wei (2001bWei ( , 2002 have studied the phenomenon of CS from various perspectives. Most studies have focused on the analysis of specific grammatical structures of CS, that is, where in a sentence the speaker may switch from one linguistic variety to another and what linguistic items can be switched.…”
Section: Models Of Codeswitchingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Tami/English: Ellaam confused-aa irundadu (Annamalai, 1989, p. 50) is an instance of CS where the English morpheme "confused" is switched into the Tami sentential frame Researchers like Poplack (1980), Joshi (1985), DiSciullo, Muysken and Singh (1986), Appel and Muysken (1987), Gardner-Chloros (1987), Azuma (1991), Myers-Scotton (1993), Grosjean (1997), Myers-Scotton (1997, 2005), MacSwan (2000MacSwan ( , 2009, Wei (2001bWei ( , 2002 have studied the phenomenon of CS from various perspectives. Most studies have focused on the analysis of specific grammatical structures of CS, that is, where in a sentence the speaker may switch from one linguistic variety to another and what linguistic items can be switched.…”
Section: Models Of Codeswitchingmentioning
confidence: 99%
“…Klavans (1983), Woodford (1983), DiSciullo et al (1986), Appel and Muysken (1987) and Pandit (1990) formulate this non-linear approach to structural constraints on CS. Appel and Muysken claim that "There cannot be a switch between two elements if they are lexically dependent on each other" (1987, p. 124).…”
Section: Government and Binding Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies (e.g. Pfaff, 1979;Di Sciullo et al, 1986;Kamwangamalu, 1989;Choi, 1991;MyersScotton, 1993a) have shown that there exist constraints on CM. Two categories are suggested for the constraints: language-specific constraints and language-universal constraints.…”
Section: E F I N I T I O N Smentioning
confidence: 99%
“…A pesar de la gran cantidad de entornos bilingües que han aportado datos sobre la alternancia de lenguas, continúa el debate sobre la naturaleza de las circunstancias que desfavorecen los cambios intra-oracionales. Dentro de la gramática generativa se ha postulado que los cambios intra-oracionales requieren una relación apropiada de reacción alrededor de la transición (DiSciullo, Muysken y Singh 1986;Belazi, Rubin y Toribio 1994). Otros investigadores han postulado la imposibilidad de permutar elementos que pertenecen a clases o categorías cerradas como pronombres, preposiciones, determinantes (Azuma y Meijer 1997;Doron 1983;Joshi 1985;Prince y Pintzuk 2000).…”
Section: Introductionunclassified